2021
DOI: 10.1038/s41598-021-97310-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing outcomes of ear molding therapy by health care providers and convolutional neural network

Abstract: Ear molding therapy is a nonsurgical technique to correct certain congenital auricular deformities. While the advantages of nonsurgical treatments over otoplasty are well-described, few studies have assessed aesthetic outcomes. In this study, we compared assessments of outcomes of ear molding therapy for 283 ears by experienced healthcare providers and a previously developed deep learning CNN model. 2D photographs of ears were obtained as a standard of care in our onsite photography studio. Physician assistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Hallac et al found that the CNN GoogLeNet could serve as an ear deformity detection model with a test accuracy of about 94.1% ( 13 ). Besides, CNN was demonstrated to be a robust tool for assessing outcomes of ear molding therapy by removing the subjectivity of human evaluation ( 14 ). Similarly, Ye et al revealed that the CNN ResNet can evaluate reconstructed auricles in a manner resembling that of a medical student, indicating the potential of CNN for assessing the outcomes of auricular reconstruction ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hallac et al found that the CNN GoogLeNet could serve as an ear deformity detection model with a test accuracy of about 94.1% ( 13 ). Besides, CNN was demonstrated to be a robust tool for assessing outcomes of ear molding therapy by removing the subjectivity of human evaluation ( 14 ). Similarly, Ye et al revealed that the CNN ResNet can evaluate reconstructed auricles in a manner resembling that of a medical student, indicating the potential of CNN for assessing the outcomes of auricular reconstruction ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complex shape and composition of the ear, it is difficult to develop mathematical models to identify deformities in the ear. Previous studies have developed CNN models to identify ear abnormalities from two-dimensional photographs with satisfactory results (13)(14)(15). To our knowledge, no CNN model has been reported to evaluate the severity of microtia, for the reported models only distinguished between normal ears and malformed ears.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the bio-metric features of the auricle are so individually specific, that make the ear shape available as another fingerprint for human recognition 12 , 13 . Researches have also been conducted to identify the auricular deformities and evaluate the corrective effects using convolutional neural networks 14 , 15 .…”
Section: Background and Summarymentioning
confidence: 99%